2018
DOI: 10.3389/fpls.2018.01128
|View full text |Cite
|
Sign up to set email alerts
|

Low Nitrogen Application Enhances Starch-Metabolizing Enzyme Activity and Improves Accumulation and Translocation of Non-structural Carbohydrates in Rice Stems

Abstract: More than 4 billion inhabitants in Asia depend on rice for 35–60% of the calories consumed in their diets, but new rice cultivars frequently do not reach expected yields because of poor rice grain filling. Here, we quantified the activities of enzymes involved in starch metabolization in rice to investigate the mechanisms regulating the accumulation and translocation of stem non-structural carbohydrates (NSC) under different levels of nitrogen fertilizer application. A pot experiment was conducted using two ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 60 publications
13
48
1
Order By: Relevance
“…This result was essentially in agreement with the previous report published by Li et al. (), who concluded that low N application enhanced the activity of starch‐metabolizing enzymes and translocation of NSCs in rice stems. In wheat and barley ( Hordeum vulgar e L.), Pheloung and Siddique () found that water stress increased the remobilization of NSC in stem tissues concomitantly with leaf senescence.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result was essentially in agreement with the previous report published by Li et al. (), who concluded that low N application enhanced the activity of starch‐metabolizing enzymes and translocation of NSCs in rice stems. In wheat and barley ( Hordeum vulgar e L.), Pheloung and Siddique () found that water stress increased the remobilization of NSC in stem tissues concomitantly with leaf senescence.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that SPS, FBPase, and Susy contributed greatly to the translocation of sucrose from stems to filling grains (Li et al., ; Wang et al., ). However, inconsistent results were reported for the correlation between the activities of sucrose‐metabolizing enzymes and NSC accumulation in stem and sheath tissues.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although protein and starch are the two primary components in flour, the ratio of protein to starch is not a strong indication of starch functionality (that is, paste viscosity). Nitrogen fertilization might increase the synthesis of enzymes (that is, starch branching enzyme, starch synthase), which are essential for starch disposition and development (Dong, Sang, Peng, Wang, & Yang, ; Dupont & Altenbach, ; Li et al., ; Rahman et al., ). Nitrogen fertilization also increases both starch content and the proportion of amylopectin in weight (Fu et al., ), leading to an increase in wholemeal flour paste viscosity (Zheng et al., ).…”
Section: The Substrate Of α‐Amylase: Starchmentioning
confidence: 99%
“…Transportation of assimilates from the source to the sink is in uenced by the function and structure of the vascular bundles, including the size, number, development and capacity ow of the bundles [12]. Environmental factors that reduce photosynthetic capacity and thereby affect the accumulation and transportation of culm NSCs such as heat stress, water de cit, low radiation level and nutrient de ciency enhances the transportation of culm NSCs [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%